2022
DOI: 10.21037/tcr-21-1957
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative blood testing for glioblastoma, brain metastases, and primary central nervous system lymphoma differentiation

Abstract: Background: Differentiating glioblastoma (GBM), brain metastases, and primary central nervous system lymphoma (PCNSL) in clinical practice is difficult. This study aimed to evaluate the diagnostic value of routine blood biomarkers in patients with GBM, brain metastases, and PCNSL and find a preoperative differential diagnostic tool for these tumors. Methods:The perioperative medical records of 70 GBM, 41 PCNSL, and 81 brain metastases patients and their preoperative blood test results were compared and analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…TT has been previously found to be a marker to differentiate brain metastases from other intracranial malignancies. 50 In this study, the prolongation of TT was positively correlated with the development of lung cancer and was significantly different between patients with lung cancer and benign lung disease ( P < 0.05), with longer TT in patients with lung cancer than in patients with benign lung disease. However, in the data collected in this study, the median values of TT in both categories of patients remained within the normal reference range.…”
Section: Discussionmentioning
confidence: 46%
“…TT has been previously found to be a marker to differentiate brain metastases from other intracranial malignancies. 50 In this study, the prolongation of TT was positively correlated with the development of lung cancer and was significantly different between patients with lung cancer and benign lung disease ( P < 0.05), with longer TT in patients with lung cancer than in patients with benign lung disease. However, in the data collected in this study, the median values of TT in both categories of patients remained within the normal reference range.…”
Section: Discussionmentioning
confidence: 46%
“…Assessment of inflammatory processes by conventional blood tests is often beneficial in the diagnosis of early stages of diseases as well as in the clinical prognosis of brain tumors [ 7 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. According to Massara et al [ 5 ], NLR higher than 4 was associated with poor prognosis when measured before standard treatments.…”
Section: Introductionmentioning
confidence: 99%
“…5,8,10 Considering the accessibility, convenience, and cost-benefit analysis among the assessing methods, biomarkers based on complete blood count (CBC) test are relatively promising in clinic because almost all the patients with brain metastases have the CBC test that is routinely measured in clinic. 8,[10][11][12][13][14] Specifically, four blood cell ratios have been highlighted by previous studies, including systemic immune-inflammation index (SII), neutrophil-to-lymphocyte ratio (NLR), platelet-tolymphocyte ratio (PLR), and lymphocyte-to-monocyte ratio (LMR) based on peripheral neutrophil, lymphocyte, monocyte, and platelet counts. A vast of studies have indicated that these four blood cell ratios could serve as potential biomarkers for cancer incidence risk, early identification of disease, prognosis, and the response to immune checkpoint inhibitors in various human malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple molecules including various types of immune cells, blood cells, and other biochemical or hematological cells have been used to map the systemic immune‐inflammation landscape in clinic and labs 5,8,10 . Considering the accessibility, convenience, and cost–benefit analysis among the assessing methods, biomarkers based on complete blood count (CBC) test are relatively promising in clinic because almost all the patients with brain metastases have the CBC test that is routinely measured in clinic 8,10–14 . Specifically, four blood cell ratios have been highlighted by previous studies, including systemic immune‐inflammation index (SII), neutrophil‐to‐lymphocyte ratio (NLR), platelet‐to‐lymphocyte ratio (PLR), and lymphocyte‐to‐monocyte ratio (LMR) based on peripheral neutrophil, lymphocyte, monocyte, and platelet counts.…”
Section: Introductionmentioning
confidence: 99%